2021
DOI: 10.1097/md.0000000000024506
|View full text |Cite
|
Sign up to set email alerts
|

Compression methods after femoral artery puncture

Abstract: Background: Vascular complications at the puncture site is a common complication after femoral artery puncture. It will not only affect the postoperative effect and patient comfort, but also may endanger the life of the patient. The effective compression hemostasis methods at the puncture site can improve the comfort of the patient, shorten the hospital stay, and reduce the burden on the medical staff. The purpose of this research is to evaluate the effectiveness and safety of different compressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…The previous study reported the incidence of pseudoaneurysms in the femoral artery in 4.5% of cases postvenous puncture with palpation (blind) method and in 2.6% of cases postultrasound-guided puncture. 6, 7 The formation of pseudoaneurysm…”
Section: Discussionmentioning
confidence: 99%
“…The previous study reported the incidence of pseudoaneurysms in the femoral artery in 4.5% of cases postvenous puncture with palpation (blind) method and in 2.6% of cases postultrasound-guided puncture. 6, 7 The formation of pseudoaneurysm…”
Section: Discussionmentioning
confidence: 99%
“…2 However, complications including hematomas, entrapment, thrombosis, arteriovenous fistulas, and pseudoaneurysms still occur when using CFA. 3 Puncture site injuries, although rare, can cause serious sequelae and may even lead to death. 4 In 2017, Kiemeneij 5 completed the world's first percutaneous coronary intervention (PCI) via left distal transradial access (dTRA).…”
Section: Introductionmentioning
confidence: 99%
“…2 However, complications including hematomas, entrapment, thrombosis, arteriovenous fistulas, and pseudoaneurysms still occur when using CFA. 3 Puncture site injuries, although rare, can cause serious sequelae and may even lead to death. 4…”
Section: Introductionmentioning
confidence: 99%
“…Among the different routes for interventional procedures, femoral artery puncture is commonly the preferred due to its high success rate, thick and straight structure, and relative stability, compared to the radial artery puncture which is less invasive but more prone to spasm and rupture (Chen et al 2021). The percutaneous puncture of the common femoral artery is widely used across various medical fields, including vascular surgery, cardiology, interventional radiology, and neuroradiology (Uhl et al 2022).…”
Section: Introductionmentioning
confidence: 99%